Methods of Improving the Reflective Abilities of Preschool Children - Abduraxmonovna, Khomidova Dilorom (European Journal of Life Safety and Stability (2660-9630), 2022)
This article analyzes issues such as the development of mature, potential, quality staff for preschool education and the development of children's interests and abilities, the use of educational technologies, methods and techniques in preparing them for quality school education, as well as the use of experience of developed countries. made.